Upaya Meningkatkan Kepatuhan Wajib Pajak Di Indonesia - Setiadi Alim Lim; Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
The success of a country in developing its country depends largely on the success of providing sufficient budget for the financing of development programs. The main sources of development financing budgets generally come from tax revenues. A country will be able to generate maximum revenue in the tax sector, if the country's tax compliance level is high. The results of research from Belkaoui (2004) showed that Indonesia was ranked 22nd out of 30 countries under study of tax compliance, with a tax compliance index of 2.53. This shows that the level of tax compliance in Indonesia is still low. Therefore, Indonesia must make various efforts to improve taxpayer compliance. The efforts undertaken must consider the factors that affect tax compliance.